2009
DOI: 10.1080/00016480902737986
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of recurrent respiratory papillomatosis from a registry of 72 patients

Abstract: Data on 72 patients were entered into an RRP database between January 2005 and July 2007. In all, 82% had already been treated for RRP in a different centre; 24 had juvenile-onset (JORRP) and 48 adult-onset (AORRP) papillomatosis. Cidovir injections had been administered to 91% of the patients. Histology found nine cases of dysplasia, one of carcinoma in situ and one of invasive carcinoma. Subglottic and tracheal locations were significantly more frequent in JORRP than in AORRP, as were the maximum Derkay scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 22 publications
(31 reference statements)
0
21
1
Order By: Relevance
“…We found that 53 (57.6%) patients had HPV6 disease and 39 (42.4%) patients HPV11 disease. The proportion of HPV11 infection in our study was slightly higher than that in previous studies where HPV11 was identified in between 8% and 39.8% of papillomas …”
Section: Discussioncontrasting
confidence: 89%
“…We found that 53 (57.6%) patients had HPV6 disease and 39 (42.4%) patients HPV11 disease. The proportion of HPV11 infection in our study was slightly higher than that in previous studies where HPV11 was identified in between 8% and 39.8% of papillomas …”
Section: Discussioncontrasting
confidence: 89%
“…Four patients (22%) in this series had undergone tracheotomy, more than the reported 0% to 10% of JORRP patients 16–18. These four tracheotomies were performed before sophisticated techniques such as the CO 2 laser became the standard of care.…”
Section: Discussionmentioning
confidence: 87%
“…Overall if HPV11 produces more aggressive disease than HPV6 the former type should be more prevalent in children (as RRP is more aggressive in children). Indeed, this HPV prevalence is implied in published data [59], [60]. Both low and high-risk HPVs are known to be associated with malignancy although high-risk types are considerably more likely to result in transformation, hence the nomenclature, ''high risk.''…”
Section: Disease Severity Defined As Need For Tracheostomymentioning
confidence: 86%